Mozambique : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report, 2015)
This Fiscal Transparency Evaluation report highlights that Mozambique's program of budget reforms has brought most aspects of its fiscal reporting and budgeting practices into line with basic and good practices, as defined under the IMF's Fiscal Transparency Code. The weaknesses on fiscal reporting could be addressed on the short term by the on-going reforms. The disclosure and management of fiscal risks are inadequate and should be improved on the medium term to face the challenges that may arise from the expected increase in natural resource revenues. This report also describes several areas in which Mozambique's fiscal transparency practices could be further improved. The institutional coverage of fiscal reports is still limited; it does not provide complete and reliable information on the operations performed by the social security fund and numerous autonomous entities, which are likely to be significant. The government's fiscal reporting is prepared on a modified cash basis, and important elements of the balance sheet, such as the current value of arrears and of shares of corporations owned by the State, are not reported. Based on the analysis, this report makes seven recommendations aimed at materially enhancing the information base for fiscal decision-making in Mozambique and ensuring the country keeps pace with evolving international transparency standards and practice.